2022
DOI: 10.1371/journal.pone.0273250
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical reasoning education in the clerkship years: A cross-disciplinary national needs assessment

Abstract: Background Improving clinical reasoning education has been identified as an important strategy to reduce diagnostic error—an important cause of adverse patient outcomes. Clinical reasoning is fundamental to each specialty, yet the extent to which explicit instruction in clinical reasoning occurs across specialties in the clerkship years remains unclear. Method The Alliance for Clinical Education (ACE) Clinical Reasoning Workgroup and the Directors of Clinical Skills Courses (DOCS) Clinical Reasoning Workgrou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Overall, our results on the contents of a CR curriculum suggest that all content is important and should be included in a CR curriculum, starting with basic theoretical knowledge and data gathering to more advanced aspects such as errors in CR and collaboration. Two other recent surveys conducted in the United States among pre-clerkship clinical skills course directors [ 12 ] and members of clerkship organizations [ 13 ] came to similar conclusions regarding the inclusion of clinical reasoning content at various stages of medical curricula. How to fit the content into already dense study programs, however, can still be a challenge [ 16 ].…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Overall, our results on the contents of a CR curriculum suggest that all content is important and should be included in a CR curriculum, starting with basic theoretical knowledge and data gathering to more advanced aspects such as errors in CR and collaboration. Two other recent surveys conducted in the United States among pre-clerkship clinical skills course directors [ 12 ] and members of clerkship organizations [ 13 ] came to similar conclusions regarding the inclusion of clinical reasoning content at various stages of medical curricula. How to fit the content into already dense study programs, however, can still be a challenge [ 16 ].…”
Section: Discussionmentioning
confidence: 64%
“…To the best of our knowledge, in addition to the work by Kononowicz et al [ 10 ], no research exists yet that addresses the needs of teachers for such a course, and Kononowicz et al [ 10 ] did not investigate their needs beyond course content. Recently, Gupta et al [ 12 ] and Gold et al [ 13 ] conducted needs analyses regarding clinical reasoning instruction from the perspective of course directors at United States medical schools, yet a European perspective is missing. Thus, our research questions were the following: What aspects of clinical reasoning are currently taught and how important are they in a clinical reasoning curriculum according to teachers and students?…”
Section: Introductionmentioning
confidence: 99%
“…This overall response rate for the clerkship leaders survey was 19% (305/1859) and ranged from 3% to 30% across specialties. Approximately 72% (220/305) percent of ACE respondents were clerkship leaders [ 16 ].…”
Section: Resultsmentioning
confidence: 99%
“…The authors previously reported separately on cross-sectional surveys of pre-clerkship clinical skills course directors serving as institutional representatives to the DOCS organization, and clerkship leaders (clerkship directors and co-directors, associate clerkship directors, and clerkship clinical site directors) from organizations that comprise ACE [ 15 , 16 ]. This report represents the analysis comparing the results from these two surveys.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation